2019
DOI: 10.1016/j.addbeh.2019.106053
|View full text |Cite
|
Sign up to set email alerts
|

Past 30-day co-use of tobacco and marijuana products among adolescents and young adults in California

Abstract: Background: Limited research among adolescents and young adults (AYA) has assessed tobacco and marijuana co-use in light of specific products. We examined the patterns of past 30-day co-use of tobacco and marijuana products, and the product-specific associations among past 30-day use of these substances. Methods: Data from three school-based convenience samples of California AYA (aged 15-22) (Sample 1=3,008; Sample 2=1,419; Sample 3=466) were collected during 2016-2017. Proportions of past 30-day co-use of tob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 34 publications
1
21
0
Order By: Relevance
“…For example, Nguyen and colleagues examined cross-sectional associations between past-month use of different types of tobacco/nicotine products and cannabis products in California youth and young adults, and found that concurrent use of ENDS + combustible cannabis and tobacco cigarettes + combustible cannabis were the most frequently reported product combinations. 17 Similarly, another cross-sectional study of young adults reported that, despite widespread availability of non-combustible T/C products, combustible methods were the most commonly-endorsed among individuals reporting past-year T/C use. 29 This is concerning because combustible product use—specifically, cigarette smoking—is associated with serious health consequences.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Nguyen and colleagues examined cross-sectional associations between past-month use of different types of tobacco/nicotine products and cannabis products in California youth and young adults, and found that concurrent use of ENDS + combustible cannabis and tobacco cigarettes + combustible cannabis were the most frequently reported product combinations. 17 Similarly, another cross-sectional study of young adults reported that, despite widespread availability of non-combustible T/C products, combustible methods were the most commonly-endorsed among individuals reporting past-year T/C use. 29 This is concerning because combustible product use—specifically, cigarette smoking—is associated with serious health consequences.…”
Section: Introductionmentioning
confidence: 99%
“…16 Mirroring findings for tobacco/nicotine products, 2 recent studies of adolescents and young adults in California found that poly-cannabis use was more common than singleproduct use. 17,18 As with tobacco/nicotine, increases in polycannabis use are concerning due to potential for greater exposure to a range of psychoactive and other harmful compounds, which could affect dependence and consequences from use. 19 Increased diversification of products has also led to more ways to co-use T/C products in combination.…”
Section: Introductionmentioning
confidence: 99%
“…Studies showed greater socio-economic status (SES) may be a risk factor for cannabis vaping [ 24 , 47 , 64 , 170 , 182 ]. E-cigarette use with nicotine only or flavors [ 28 , 29 , 163 , 166 , 172 174 , 180 , 186 , 197 •, 198 , 200 ], as well as use of cigarettes, cigars, hookah, and smokeless tobacco [ 21 , 28 , 29 , 50 , 163 , 166 , 174 , 178 , 179 , 186 , 195 , 197 •, 199 ] is associated with greater odds of cannabis vaping. Former cannabis use, susceptibility to use cannabis, and peer use of cannabis, via vaping and other forms of cannabis consumption (e.g., ingesting, smoking), have also been shown to be related to greater odds of cannabis vaping [ 21 , 169 , 170 , 173 , 175 , 179 , 180 , 184 , 200 ].…”
Section: Resultsmentioning
confidence: 99%
“…28 Co-use of tobacco and cannabis is even higher than tobacco use alone among California's young people. 29 In the general population, cannabis use is associated with persistent cigarette smoking, high nicotine dependence, and low cessation among cigarette smokers. 30 Likewise, a study among the SUD population found that ever users of blunt/spliff were less likely to plan to quit in the next 30 days.…”
Section: Discussionmentioning
confidence: 99%